2003
DOI: 10.1037/h0087431
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Perceptual Distinctiveness on the Prospective and Retrospective Components of Prospective Memory in Young and Old Adults.

Abstract: In two experiments, the effect of perceptual distinctiveness of cues on prospective memory performance was examined. Young and older adults completed a visual search task with embedded prospective memory instructions. On each trial, participants were asked to indicate the position of a target letter in a letter string, unless either of two letters previously identified as prospective memory cues was presented. Each prospective cue was associated with a specific response. Perceptual distinctiveness was manipula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
41
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 37 publications
(34 reference statements)
7
41
0
Order By: Relevance
“…We administered two distinct eventbased tasks, together with a similar ongoing task, to assess the ProCom and RetCom separately, as far as possible, using a direct measure. In the literature, the ProCom has often been assessed with an indirect measure, only relevant when both components are preserved: When the participants fail to carry out the prospective task, the experimenter asks them if there is something they are meant to do (i.e., he or she compensates for a possible ProCom impairment by helping them to remember when to do something, and ProCom is never assessed independently; Livner et al, 2009;Adda et al, 2008;Costa et al, 2008;Carlesimo et al, 2004;Cohen et al, 2003). This only allows ProCom integrity to be assessed if the RetCom is preserved, too (i.e., the participant performs the correct prospective task at the appropriate time).…”
Section: Prospective Memorymentioning
confidence: 99%
See 1 more Smart Citation
“…We administered two distinct eventbased tasks, together with a similar ongoing task, to assess the ProCom and RetCom separately, as far as possible, using a direct measure. In the literature, the ProCom has often been assessed with an indirect measure, only relevant when both components are preserved: When the participants fail to carry out the prospective task, the experimenter asks them if there is something they are meant to do (i.e., he or she compensates for a possible ProCom impairment by helping them to remember when to do something, and ProCom is never assessed independently; Livner et al, 2009;Adda et al, 2008;Costa et al, 2008;Carlesimo et al, 2004;Cohen et al, 2003). This only allows ProCom integrity to be assessed if the RetCom is preserved, too (i.e., the participant performs the correct prospective task at the appropriate time).…”
Section: Prospective Memorymentioning
confidence: 99%
“…However, these two components are difficult to study separately in two different but comparable tasks. Previous studies have encountered this very difficulty, for although they have been able to assess the RetCom by giving participants a clue to compensate for any ProCom deficit (Livner, Laukka, Karlsson, & Backman, 2009;Adda, Castro, Alem-Mar e Silva, de Manreza, & Kashiara, 2008;Costa, Peppe, Caltagirone, & Carlesimo, 2008;Carlesimo, Casadio, & Caltagirone, 2004;Cohen, Dixon, Lindsay, & Masson, 2003), but these paradigms did not assess the ProCom directly.…”
Section: Introductionmentioning
confidence: 99%
“…time-monitoring, task inhibition and task switching) within these two PM phases (e.g. Cohen et al 2003;Kliegel et al 2004;Raskin et al 2011). In contrast, the phase of intention formation has rather been neglected.…”
mentioning
confidence: 99%
“…Cherry & Plauche, 2003;Cohen, Dixon, Lindsay, & Masson, 2003;Cohen, West, & Craik, 2001;McDaniel, Einstein, Stout, & Morgan, 2003). Among various proposed explanations for age differences, West and Craik (1999) suggested that after encoding, intentions may momentarily fall below consciousness and fluctuate over the course of task performance.…”
mentioning
confidence: 99%